Genetically Modified Mouse Models of Congenital Diaphragmatic Hernia: Opportunities and Limitations for Studying Altered Lung Development - Friedmacher, Florian; Rolle, Udo; Puri, Prem (Frontiers in Pediatrics, 2022)
Congenital diaphragmatic hernia (CDH) is a life-threatening defect in the integrity of the fetal diaphragm that interferes with normal lung development. As a result, CDH is almost invariably accompanied by immature and hypoplastic lungs, which are one of the leading causes of morbidity and mortality in patients with this condition. In recent decades, animal models have played an invaluable role in improving our understanding of the genetic mechanisms underlying CDH and associated pulmonary hypoplasia. In particular, the creation of genetically modified mouse models, which show both diaphragm and lung abnormalities, has resulted in the discovery of many important candidate genes and signaling pathways implicated in the pathogenesis of CDH. This article aims to offer an up-to-date overview on CDH-implicated transcription factors, molecules involved in cell migration and components of the extracellular matrix, whilst also discussing the significance of these genetic models for studying altered lung development in relation to the human situation.